Desertification in Arid Regions: Drivers, Impacts, and Sustainable Management Strategies with a Focus on Central Asia - Y.D, Kholov; F, Farmonova; Z, Sharipova; Sh., Komiljonova (American Journal of Biology and Natural Sciences, 2026)
Desertification represents a major environmental and socio-economic challenge in arid and semi-arid regions worldwide. This study provides a comprehensive analysis of desertification processes, their climatic and anthropogenic drivers, and their ecological and socio-economic impacts, with particular emphasis on Central Asia and Uzbekistan. The research integrates interdisciplinary approaches, including ecological assessment, climate analysis, and land-use evaluation. The findings indicate that desertification is primarily driven by unsustainable land use practices combined with climate change, leading to soil degradation, biodiversity loss, and reduced agricultural productivity. The study proposes sustainable land management strategies, efficient water use practices, and the application of modern technologies such as GIS and remote sensing to mitigate desertification. The results highlight the importance of integrated policy frameworks and regional cooperation in addressing land degradation and ensuring long-term sustainability.